Pitch Pitch ratio effect on the effectiveness of condenser for essential oil distillation - Nicolas Titahelu; Jonny Latuny; Cendy Sophia Edwina Tupamahu; Sefnath Josep Etwan Sarwuna (University of Muhammadiyah Malang, 2021)
This research is focused on the usage of the helical coil pipe to shorten the distillation time which then aimed to obtain a helical coil pipe condenser configuration with an effective pitch ratio to shorten the distillation time. The pitch ratio value is varied from 2.10 to 4.20. The experimental results show that the effectiveness of the condenser decreases as the pitch ratio increases, where the maximum effectiveness at the pitch ratio of 2.10 is 74.13%, while the minimum pitch ratio of 4.20 is 67.19%. The maximum effectiveness is obtained at a pitch ratio of 2.10 due to a larger heat transfer contact area which results in an increase in the actual heat transfer as well. The experimental results with a pitch ratio of 2.10 obtained a condensate temperature of 37.29 °C which is 22.71 °C and a distillation time of only 2 hours compared to the results of the straight pipe condenser used by the SME group. The effect of the helical coil pipe pitch ratio obtained from the experimental results with a mean deviation value of 2.81% compared to the numerical study. It is concluded that the maximum condenser effectiveness is at the minimum pitch ratio value and then the pitch ratio of 2.10 can be used for the clove essential oil distillation process.